Shedding Light on the Dentition and Venom Delivery System of the Rear-Fanged Snake, Galvarinus chilensis chilensis (Serpentes: Dipsadidae: Tachymenini) from Chile - Herrera, Yarela (2022)
Although the rear-fanged snake Galvarinus chilensis chilensis (formerly named Tachymenis ch. chilensis) causes ophidian accidents with clinical importance in Chile, the anatomical and histological characterizations of the venom delivery system (venom gland and fang) of this species still remain unknown. This study describes the dentition and characteristics of fangs and their ontogenetic variations in G. ch. chilensis. Moreover, histological and histochemistry analyses of the venom glands of this species are presented. Using micro-computed tomography and scanning electron microscopy, the dentitions of neonates, juveniles, and adults were analyzed, and no ontogenetic variations in teeth length and number present in the dentary and maxilla were observed. Moreover, we found three types of basic teeth, with distributional patterns conserved in all ontogenetic categories. The fangs exhibited a groove from the base to the middle. At the end of the groove, prominent ridges are formed. The fang and groove lengths were significantly distinct between ontogenetic categories. No differences between females and males were observed. Histologically, we found that the venom gland is close to the fangs and has a seromucous composition. Our results describe, for the first time, the distributional pattern and characteristics of the dentition and venom delivery system of the poorly studied snake G. ch. chilensis.